PENGARUH HUMAN CAPITAL TERHADAP BUSINESS PERFORMANCE MELALUI CUSTOMER CAPITAL - Juwita, Siti Pritiza; Anggraini, Fivi (UI Scholars Hub, 2007)
The purpose o f this research is to investigate the effect o f human capital on business performance with customer capital as the intervening variable. Samples used in this research are commodity export companies listed in The Industry and Trade Provincial Office o f West Sumatera. Data used for this research was collected from financial managers and personnel managers that completing and returning the questionnaire. Data collected by mail survey and contact person with 70 questionnaire and respon rate 38 questionnaires (54%). Analysis conducted by path analysis technique and software SPSS 12.00. The result shows that human capital positively but not significantly linked with customer capital; customer capital positively but not significantly linked with business performance; and human capital does not related with business performance with customer capital as the intervening variable.